English Teachers' Pedagogic Competence in Digital Literacy in Senior High School Setting - Kiki Nur Ais; Eline Rozaliya Winarto; Susilawati Susilawati (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2023)
This study aimed to identify the pedagogic competence of teachers from different school context in employing digital literacy. To achieve this goal, qualitative research by involving observation and interview as the data collection technique. The result revealed that both teachers met six of the seven measures of teacher pedagogical ability. This study, afterward, used qualitative design. After conducted the research, the researchers drew conclusion that teachers’ upgrading in digital literacy is very important. Both private and state schools that have been observed, all teachers are equiped enough in digital literacy. Both English teachers employed digital literacy in all section of pedagogic competence including to master the characteristics of student, learn theory and principle, develop curriculum, carry out lesson plans, develop the potential students, communicate effectively with students, evaluates the process and learning outcomes of student.